Neck Muscle Changes Following Long-Duration Spaceflight - McNamara, Kyle P.; Greene, Katelyn A.; Tooze, Janet A.; Dang, Jade; Khattab, Karim; Lenchik, Leon; Weaver, Ashley A. (Frontiers in Physiology, 2019)
The effects of long-duration spaceflight on crewmember neck musculature have not been adequately studied. The purpose of this study was to evaluate the changes in the neck musculature on pre-flight and post-flight magnetic resonance imaging (MRI) examinations of six crewmembers on 4- to 6-month missions equipped with the advanced Resistive Exercise Device. The MRI images were resliced to remove variations in spinal curvature, and the cross-sectional area (CSA) and muscle fat infiltration (MFI) of neck musculature at the C1-C2, C4-C5, C7-T1, and T1-T2 intervertebral disc levels were measured bilaterally. Percent changes in the neck muscle CSA and fatty infiltration following spaceflight were calculated, and mixed models were used to assess significance of these changes. Crewmembers on missions equipped with the advanced Resistive Exercise Device experienced an average 25.1% increase in CSA for the trapezius muscle at C6-C7, an average 11.5% increase in CSA for the semispinalis capitis muscle at C4-C5, an average 9.0% increase in CSA for the sternocleidomastoid muscle at C4-C5, and an average 23.1% increase in CSA for the rhomboid minor at T1-T2. There were no significant changes in the CSA of the levator scapulae, splenius capitis, rectus capitis posterior major, scalenus anterior, scalenus posterior, scalenus medius, longissimus capitis, or obliquus capitis inferior muscles at the locations measured. None of the muscles analyzed experienced statistically significant changes in fatty infiltration with spaceflight. Our study indicates that long-duration spaceflight conditions are associated with preservation of cross-sectional area in most neck muscles, and significant increases in the cross-sectional areas of the trapezius, semispinalis capitis, sternocleidomastoid, and rhomboid minor muscles. This may indicate that cervical muscles are not subjected to the same degradative effects microgravity imparts on the majority of muscles.